Застосування надпровідних накопичувачів для демпфування нерегулярних коливань перетоку потужності - Васецький, Ю.М.; Мазуренко, І.Л.; Павлюк, А.В. (Технічна електродинаміка, 2012)
Possibility of use of SMES as dynamic active means for damping of low-frequency irregular power fluctuations in electric power system is shown. Regulation parameters are chosen, energy as well as mass and size parameters of new configuration SMES are defined. At the proposed regulation way characteristic period of non compensated fluctuations corresponds to chosen time of smoothing and it frequency is not dangerous to occurrence of emergency mode of operation.